The Role of Agricultural Innovation Investment in Enhancing Food Security: Evidence from Yogyakarta - Durohman, Hapid (SMART Insight, 2025)
This study investigates the effect of agricultural innovation, proxied by public agricultural R&D expenditures and the number of agricultural researchers, on food security outcomes in the Special Region of Yogyakarta (DIY), Indonesia. Using a panel dataset covering five districts from 2010 to 2023, the study applies the bootstrapped Least Squares Dummy Variable (LSDV) estimator to control for unobserved district and time effects and to enhance the robustness of inference. Food security is measured by per capita caloric intake, while innovation inputs are drawn from local government and agricultural agency records. The results indicate that agricultural innovation has a statistically significant and positive impact on food security. Among the innovation variables, the number of agricultural researchers shows a more consistent and stronger association with increased dietary energy consumption than R&D spending, underscoring the importance of human capital in converting scientific advancements into tangible outcomes. The findings highlight that even in regions with modest agricultural output, such as Yogyakarta, institutional support, knowledge dissemination, and effective extension services can enhance the benefits of innovation. The study recommends increased investment in researcher capacity and improved coordination among provincial research stakeholders to achieve inclusive and sustainable food security improvements.